Vaginal leiomyoma - Indranil Chakrabarti; Anuradha De; Shyamapada Pati (Wolters Kluwer Medknow Publications, 2011)
Leiomyomas are common benign tumors in the uterus. However, vaginal leiomyomas remain an uncommon entity with only about 300 reported cases. Here, we report a case of a 38-year-old multigravida who presented with lower abdominal pain and vaginal bleeding. A physical examination and ultrasonography were performed, and a diagnosis of cervical fibroid was made. Pervaginal removal of the tumor was performed and subsequent histopathology revealed a vaginal leiomyoma. Although a rare tumor, vaginal leiomyomas may present with a variety of clinical features and may be mistaken preoperatively for cervical fibroid. Removal of tumor by vaginal route, wherever possible, with subsequent histopathological examination appears to be the optimum management plan.